2023
DOI: 10.1002/pchj.632
|View full text |Cite
|
Sign up to set email alerts
|

The dark triad, performance avoidance, and academic cheating

Abstract: This study found that: (1) performance avoidance played a partial mediating role between college students' psychopathy, Machiavellianism, and academic cheating, respectively; and(2) performance avoidance showed a full mediating role between college students' narcissism and academic cheating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Additionally, both narcissism and psychopathy were positively related to the intention to use chatbot-generated texts, indicating that individuals who are self-focused and unemotional are more inclined to use chatbot technology for personal gain. Some previous studies have shown that Machiavellianism, but not psychopathy [ 19 ] or narcissism [ 17 , 18 ], is related to academic cheating. The present findings corroborate other previous work showing that all Dark Triad traits are positive predictors of academic misconduct [ [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, both narcissism and psychopathy were positively related to the intention to use chatbot-generated texts, indicating that individuals who are self-focused and unemotional are more inclined to use chatbot technology for personal gain. Some previous studies have shown that Machiavellianism, but not psychopathy [ 19 ] or narcissism [ 17 , 18 ], is related to academic cheating. The present findings corroborate other previous work showing that all Dark Triad traits are positive predictors of academic misconduct [ [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown positive links between all Dark Triad traits and academic misconduct [ [14] , [15] , [16] ]. However, other studies [ 17 , 18 ] found that academic cheating was significantly positively correlated with psychopathy and Machiavellianism, but not with narcissism. In another study [ 19 ], Machiavellianism and narcissism were positively associated with self-reported academic cheating behaviors, whereas psychopathy was not.…”
Section: Introductionmentioning
confidence: 88%